Case Report: A Novel Deletion in the 11p15 Region Causing a Familial Beckwith–Wiedemann Syndrome - Chen, Juan; Xu, Jian; Yu, Yang; Sun, Ling (Frontiers in Genetics, 2021)
Beckwith-Wiedemann syndrome (BWS; OMIM 130650) is a human overgrowth and cancer susceptibility disorder with a wide clinical spectrum, which cannot be predicted based on genomic variants alone. Most reports on BWS cases focus on childhood patients. Studies on adult BWS patients are scarce. Our study reports a BWS family in which the disorder appears to be caused by deletion of H19 and its upstream regulatory elements. Genetic analysis showed a heterozygous microdeletion (~chr11:2009895-2070570 (GRCh37)) in the patients. Maternal deletion in H19 can result in loss of function of the IGF2-H19 imprinting control element, which leads to BWS. The male proband in this family was affected by the testicular anomaly and cryptorchidism. Early orchidopexy did not rescue his azoospermia, which might be not the consequence of cryptorchidism, but due to genetic defects associated with H19 deletion. In summary, our study gives some insights on the presentation of BWS in adulthood.